A Recently Patented Sleeve-Type Endotracheal Tube: Innovative Design and Clinical Prospects for Improving One-Lung Ventilation - Zhang S; Li N; Su N; Yun L; Li L; Zhi J; Lin Q; Zhu M; Li K; Zhao Z (Medical Devices: Evidence and Research)
Shengmao Zhang,1,* Na Li,2,* Nan Su,1 Letian Yun,1 Lele Li,1 Jing Zhi,1 Qihang Lin,1 Mengxin Zhu,1 Keer Li,1 Zhihui Zhao1 1Inner Mongolia People’s Hospital, Hohhot, Inner Mongolia Autonomous Region, People’s Republic of China; 2Pain Department, Hohhot First Hospital, Hohhot, Inner Mongolia Autonomous Region, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhihui Zhao, Inner Mongolia People’s Hospital, Hohhot, Inner Mongolia Autonomous Region, People’s Republic of China, Email 18904501839@163.comAbstract: The Sleeve-Type Endotracheal Tube (STET) is an innovative airway management device designed to address the limitations associated with traditional double-lumen tubes (DLTs) and bronchial blockers (BBs). Utilizing a modular structure comprising an outer sheath tube, inner sheath tube, and blocking tube, the STET offers increased flexibility in one-lung ventilation (OLV) and airway clearance, thereby reducing airway trauma and improving ventilation efficiency. Its dual-cuff system ensures stable positioning, while its versatile design accommodates diverse patient populations, including pediatric patients and those with difficult airway anatomy. This review explores the structural characteristics, manufacturing processes, clinical advantages, potential limitations, and practical applications of the STET. After multiple rounds of structural optimization, the STET design has successfully advanced into pilot production. Preliminary validation results from small-scale manufacturing and functional testing demonstrate promising structural stability, operational flexibility, and safety performance. The STET represents a significant advancement in airway management, holding substantial potential to improve patient outcomes and transform clinical practice in thoracic surgery and critical care anesthesiology.Keywords: sleeve-type endotracheal tube, one-lung ventilation, airway management, modular design, thoracic surgery